Kebijakan Manajemen Lembaga Pendidikan dalam Meningkatkan Mutu Pendidikan Islam - Abdul Mukti; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Departement of Mathematics Education, 2024)
This exploration plans to depict Schooling The executives Strategy in Working on the Nature of Islamic Training. The sort of examination in this paper is expressive subjective. The information assortment methods utilized were interviews and furthermore different sources from pertinent books and diaries. The exploration results show that the execution of instructive administration requires a long cycle and includes many gatherings. This progress requires changes, the two frameworks (structure), culture and figures, to the new requests of school-based administration. Subsequently, we don't dream that this change will be an oddball and produce great outcomes. Accordingly, adaptability and trial and error that produce additional opportunities in the use of school-based administration should be energized. The arrangement of executing school-based administration in working on the nature of Islamic training is a certainty that should be carried out right away. The pith of independence in addition to participatory direction. will likely engage madrasas. arrangements in working on the nature of Islamic training can be sequenced as follows: mingling the idea, doing objective examination, recognizing the capabilities expected to accomplish targets, completing SWOT examination, planning madrasa plans, executing madrasa designs and forming new targets